HUBUNGAN ASUPAN PROTEIN, VITAMIN C, ZAT BESI, DAN KEBIASAAN MINUM TEH DENGAN KADAR HB SISWA PUTRI KELAS X DAN XI DI SMA PL DON BOSKO SEMARANG - Annisa Nurhayu; Basuki Sigit Budi Prabowo; Sri Noor Mintarsih (Poltekkes Kemenkes Semarang, 2014)
Background : Iron nutritional anemia is anemia that arises due to the absence of the body's ironreserves so that the supply of iron for the formation of erythropoesis is reduced, so that eventually the formation of hemoglobin will decrease. The anemia prevalence in adolescent girls in 2011 in Semarang city was 5%. Based on observations in February 2013 at Don Bosko High School, the prevalence of iron deficiency anemia was 20%. Objective : The purpose of this study was to determine the relationship of protein intake, vitamin C, iron, and tea drinking habits with Hb levels. Method : This type of research is explanatory research with a case-control approach with a ratio of 1: 1 (matching age). The sample was 28 female students taken by simple random sampling. Primary data includes sample identity, anthropometric data, protein intake, vitamin C intake, iron intake, tea drinking habits, and Hb levels. Secondary data includes an overview of the location of the study. Protein, vitamin C, iron intake, and tea drinking habits were obtained using the Semi Quantitative Food Frequency form, while Hb levels were measured using the chyanomethoglobin method. Data analysis using Mc statistical test. Nemar. Result : The results showed that there were 67.89% samples of good protein intake, 64.29% of samples of vitamin C intake were good, 82.14% of samples of iron intake were not good, and 78.57% of samples of tea drinking habits were not good. There was no relationship between protein intake and Hb levels (p = 0.453, OR = 2.5). There is a relationship between vitamin C intake and Hb levels (p = 0.031). There was no association between iron intake and Hb levels (p = 1,000, OR = 1.5). There is no relationship between tea drinking habits and Hb levels (p = 0.500).